2021
DOI: 10.1016/j.foot.2020.101771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corrective insole on leg muscle activation and lower extremity alignment in rice farmers with pronated foot: a preliminary report

Abstract: Background: Execution of strenuous activities in conjunction with slippery and viscous muddy working terrain in rice cultivation leads to a high prevalence of farmer musculoskeletal disorders and malalignments. Recommended intervention strategies originally designed for congenitally disabled individuals may also be applicable to farmers, including simple corrective wedges to reduce foot eversion. The objective of the present study was to conduct a preliminary investigation of the effects of corrective wedges o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This study addresses participatory ergonomic interventions recommended for an annual peach farming cycle in a Korean farming organization. Most existing studies focus on interventions for parts of the agricultural work, such as pruning, load carrying, harvesting, and sorting [2,[15][16][17][18][19][20][21][22][23][24][25]. In contrast, an ergonomic analysis was conducted for all tasks performed during the entire agricultural work cycle of peach farming in this study, and interventions were proposed based on the results of the ergonomic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study addresses participatory ergonomic interventions recommended for an annual peach farming cycle in a Korean farming organization. Most existing studies focus on interventions for parts of the agricultural work, such as pruning, load carrying, harvesting, and sorting [2,[15][16][17][18][19][20][21][22][23][24][25]. In contrast, an ergonomic analysis was conducted for all tasks performed during the entire agricultural work cycle of peach farming in this study, and interventions were proposed based on the results of the ergonomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Pranav and Patel [16] developed an ergonomic tool for manual harvesting of oranges in hilly regions. Other ergonomic-intervention-related studies include ergo bucket carriers and easy lift [17]; an apple picking bucket [18]; handglove materials for farming activities [19]; magnifier inspection, a lift assist system, and a smokeless method for calming bees in apiculture [20]; corrective insoles [21]; ergonomic baskets for tealeaf plucking [22]; and ergonomic interventions for weeding, weighing beef calves, and growing vegetables [23][24][25]. Fathallah [2] reviewed the extent of MSDs in agriculture and employed a historic perspective on how ergonomic interventions have been used to reduce the health effects of labor-intensive agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…In a review found in the literature, it is shown that in adults with different pathologies such as cavus foot, rheumatoid arthritis (RA), the custom-made foot orthosis reduces the patient's pain [4].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies found in the literature that evaluate the efficacy of plantar orthoses, but all are focused on certain pathologies or alterations, most of these studies are focused on treating very specific alterations of the foot [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors employ low-cost prefabricated insoles which only consider foot size [1,2]. In contrast, others consider customizing prefabricated insoles by adding medial or lateral wedges [3,4], and custom-made insoles manufactured through foot casting aim to position the subtalar joint in neutral [5,6]. There are many prescriptions for insoles with different purposes that have been researched and used clinically.…”
Section: Introductionmentioning
confidence: 99%